Measurement of the top quark mass in the all-hadronic mode at CDF - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
A measurement of the top quark mass (M top) in the all-hadronic decay channel is presented. It uses 5.8 fb -1 of pp data collected with the CDF II detector at the Fermilab Tevatron Collider. Events with six to eight jets are selected by a neural network algorithm and by the requirement that at least one of the jets is tagged as a b-quark jet. The measurement is performed with a likelihood fit technique, which simultaneously determines M top and the jet energy scale (JES) calibration. The fit yields a value of M top=172.5±1.4(stat)±1.0(JES)±1.1(syst) GeV/c 2. © 2012 Elsevier B.V.